A Comparative Study of Technology Integration in EFL Classrooms in Public and Vocational High Schools in Indonesia - Warda Lessy; Lailatul Qadriyah Umarella (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study examines how technology is used in English as a Foreign Language (EFL) classrooms in public and vocational high schools in Indonesia, focusing on teachers' practices and the challenges they face. Using a quantitative approach with a sample of 30 EFL teachers, the findings show that both groups are comfortable and skilled in using technology. However, vocational schoolteachers report significantly higher levels of technology integration and access compared to public school teachers. Key factors affecting technology integration include access to technology, technical skills, and effective integration practices. The results highlight the need for targeted professional development and resource allocation to promote fair technology integration in education. Ultimately, this improvement aims to enhance EFL instruction and better prepare students for a competitive global environment.